Phosphorus-drought interaction modulates growth dynamics and essential oil biosynthesis in Rosmarinus officinalis - Alfalah, Mohamed; Bouharroud, Rachid; Beniaich, Adnane; El Aroussi, Fatima; El Gharous, Mohamed; Lyamlouli, Karim (Frontiers in Plant Science, 2025)
This study aimed to investigate the combined effects of drought stress and phosphorus fertilization on the morphological, physiological, and biochemical traits of R. officinalis, with a focus on essential oil yield and composition. Rosemary plants were subjected to three irrigation levels (I1=80%FC; I2=50%; I3: 30% of soil moisture content at field capacity), and three phosphorus levels (P10=10 kg/ha; P25=25 kg/ha; P50= 50 kg/ha). Increasing drought stress significantly reduced growth indicators such as leaf area index (LAI), stem length, stem diameter, root and shoot biomass, and root traits, while moderate drought induced root elongation, indicating adaptive responses. Phosphorus significantly influenced stem diameter and LAI. Drought stress altered stomatal conductance and chlorophyll content, but these were maintained under moderate phosphorus supply and moderate water stress (I2P25). This treatment also resulted in the highest essential oil yield, up to 113%, compared to well-watered controls. Furthermore, I2P25 markedly enhanced the accumulation of key oxygenated monoterpenes, with relevant increases in endo-borneol, l-α-terpineol, verbenone, camphor, terpineol, and linalool. In contrast, severe drought shifted the oil profile toward monoterpene hydrocarbons. Principal Component Analysis confirmed distinct metabolic clustering at I2P25, indicating an optimal balance between stress and nutrient availability. These findings suggest that moderate drought coupled with optimal phosphorus supply improves essential oil quality and yield without compromising biomass, offering a sustainable cultivation strategy for rosemary in water-limited environments. Principal Component Analysis (PCA) supported this result, revealing distinct grouping under moderate drought (I2) and optimal phosphorus doses (P25), consistent with a metabolic tipping point marked by enhanced biosynthesis of oxygenated monoterpenes. These findings suggest that moderate drought, in combination with optimal phosphorus input, can improve essential oil quality and yield without severely compromising biomass, providing a strategic cultivation approach for rosemary under water-limited environments.